The Influence of Knowledge Processes on the Innovativeness of Technology and Engineering Consultancies - Ojanen, Ville; Xin, Yan; Chai, Kah-Hin; Tan, Ivan (International Journal of Industrial Engineering and Management, 2011)
Technology and engineering consultancies (TEC) are knowledge-intensive entities which rely on effective project management and system integration to compete successfully. Increasingly, these firms are becoming pivotal in the economies of numerous countries. However, how these firms operate, particularly in terms of innovation management, remains largely unknown. A review of the literature suggests that efficient knowledge management is critical for the innovativeness of TEC firms. This paper seeks to examine the impact of the various stages of knowledge management, i.e. knowledge acquisition, dissemination, and utilization, on the innovativeness of TEC firms in Singapore, by drawing on results from conducted qualitative and quantitative studies including questionnaires mailed to TEC firms in Singapore. The findings suggest that knowledge acquisition and knowledge utilization have a positive impact on the innovativeness of TEC firms and also that this impact is stronger for firms operating in more volatile environments. This could mean that TEC firms are relying on having a large portfolio of existing projects that can be reused rather than innovating from first principles. However, this may not be sufficient for TEC firms to remain innovative in the long run, especially when their clients are lead users in their industry. Article history: Received (10.06.2011); Revised (28.10.2011); Accepted (28.10.2011)